2004
DOI: 10.1128/mcb.24.9.3607-3622.2004
|View full text |Cite
|
Sign up to set email alerts
|

Akt2, a Novel Functional Link between p38 Mitogen-Activated Protein Kinase and Phosphatidylinositol 3-Kinase Pathways in Myogenesis

Abstract: Activation of either the phosphatidylinositol 3-kinase (PI 3-kinase)/Akt or the p38 mitogen-activated protein kinase (MAPK) signaling pathways accelerates myogenesis but only when the reciprocal pathway is functional. We therefore examined the hypothesis that cross-activation between these signaling cascades occurs to orchestrate myogenesis. We reveal a novel and reciprocal cross-talk and activation between the PI 3-kinase/Akt and p38 MAPK pathways that is essential for efficient myoblast differentiation. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 70 publications
4
92
1
Order By: Relevance
“…This is consistent with the emerging concept that PI3K/Akt signaling has diversified capacities and is apparently capable not only to promote cell growth but also to contribute in cell differentiation. Indeed, recent studies reported that activation of the PI3K/Akt pathway is required for the differentiation of myoblasts (Cabane et al, 2004;Gonzalez et al, 2004;Sarker and Lee, 2004), keratinocytes (Calautti et al, 2005) as well as for the RA-induced differentiation of neuroblastoma cells (Lopez-Carballo et al, 2002), HL60 cells (Ishida et al, 2004), endometrial adenocarcinoma cells (Carter, 2003) and APL cells (Lal et al, 2005). The precise mechanisms through which the PI3K/Akt pathway contributes to cell differentiation have not been determined yet.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the emerging concept that PI3K/Akt signaling has diversified capacities and is apparently capable not only to promote cell growth but also to contribute in cell differentiation. Indeed, recent studies reported that activation of the PI3K/Akt pathway is required for the differentiation of myoblasts (Cabane et al, 2004;Gonzalez et al, 2004;Sarker and Lee, 2004), keratinocytes (Calautti et al, 2005) as well as for the RA-induced differentiation of neuroblastoma cells (Lopez-Carballo et al, 2002), HL60 cells (Ishida et al, 2004), endometrial adenocarcinoma cells (Carter, 2003) and APL cells (Lal et al, 2005). The precise mechanisms through which the PI3K/Akt pathway contributes to cell differentiation have not been determined yet.…”
Section: Discussionmentioning
confidence: 99%
“…Such cross-talk between the MAPK and PI3K signaling pathways has already been described. 46 Interestingly, the PI3K inhibitor LY294002 markedly increased the amount of STAT3 activation achieved by stimulating cells with IL-6 (Figure 6c), suggesting that activation of …”
Section: Pi3k and Mapk Activation In Mt-ret Melanomasmentioning
confidence: 99%
“…Akt Activity Controls Differentiation of C2C12 and 3T3-L1 Cells-Akt activity has been implicated in differentiation of preadipocytes and myoblasts (25)(26)(27)(28)(29)(30)(31). As expected, Akt was activated during differentiation as seen by increased phosphorylation at Ser-473 (Fig.…”
Section: Comparisons Of Pyst and Svst Two Polyomavirus Small T Antigmentioning
confidence: 66%
“…Both Akt1 and Akt2 play a role in myoblast differentiation (28,30,31), and knockdown of either blocks myoblast differentiation (30,31). Conversely, Akt2 expression is increased during the differentiation process (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation